Massive regularization for effective tax payment: Evidence from Brazil - Anastasiya Yarygina; Eduardo Iketani; Andre Martinez; Ernesto Tiburcio (Inter-American Development Bank (IDB), 2025)
In recent years, tax administrations around the globe have leveraged digital transformation to enhance processes and services to improve tax compliance. Massive self-regularization platforms, which identify noncompliant taxpayers, notify them about the detected inconsistencies, and allow them to amend the situation with the tax authority, are prominent examples of the digital transformation of tax administrations. This study presents the results of the randomized controlled trial evaluating the effectiveness of such a self-regularization platform in the Brazilian State of Para. The results show that the platform increased the amount of the taxes paid by 12.78 times and the probability of tax compliance by 236 percent. Overall, the effectiveness of self-regularization in recovering the evaded tax is 60 percent higher than that of the traditional audit-based approach. The amount of the correction in the declared tax increased by 2.33 times, and the probability of correction by 300 percent. Given the low marginal cost of self-regularization, the results suggest that these platforms are a remarkable opportunity for tax administrations to leverage digital transformation effectively and efficiently, improving tax compliance and increasing tax revenue.
Keywords: H26; H30; H32; O38; 330; digitalization; tax compliance; taxpayer support